Un'ancella di INSPIRE: BRISEIDE - Salvemini, Mauro (GEOmedia, 2010)
BRISEIDE, INSPIRE's maid BRISEIDE (BRIdging SErvices, Information and Data for Europe)” aims at delivering (1) time-aware extension of data models developed in the context of previous/ongoing EU INSPIRE related projects (e.g. in the context of GMES, eContentPlus), (2) application (e.g. Civil Protection) based on the integration of existing, user operational information and (3) value added services for spatio-temporal data management, authoring, processing, analysis and interactive visualisation.